Australian queer screen stakeholders and creative artists: perceptions of value, motivation and impact of LGBTQ+ Australian film. Issue 1 (2nd January 2022) - Cover, Rob
ABSTRACT: This paper reports findings from interviews with key Australian stakeholders involved in Australian films with gender- and sexually-diverse (LGBTQ+) characters, themes and narratives. The paper found that directors, creative producers, screenwriters and actors involved stakeholders of Australian LGBTQ+ film expressed a desire to impact their audiences in ways that emphasise the value of entertainment texts for minority representation, pedagogy and social change beyond pure storytelling. This paper presents an account of three key frameworks through which film stakeholders expressed their understanding of – and motivation towards – impact beyond storytelling: (i) as filling a gap in LGBTQ+ representation in contrast to what was otherwise perceived as relative invisibility; (ii) their perception as stakeholders dealing with LGBTQ+ content as having a special role as 'educators' for the benefit of vulnerable youth; and (iii) an understanding of their texts as contributing to social change in Australia, including wider acceptance of LGBTQ+ persons, family members and communities. A significant finding from this study is that screen media films about LGBTQ+ topics continue to be perceived as playing a role connected with but exceeding entertainment.